Asma Binti Abu Bakar and the Hadith on Inter- Religious Relations: Perspectives in Contemporary Societies - Binte Sellamat, Nenny Suzanah; Ariffin, Tajul; Kosasih, Engkos (TAQNIN: Jurnal Syariah dan Hukum, 2024)
Introduction: Inter-religious relations is a key factor to ensure peace and harmony, nationally and globally. Throughout history, there were many examples of religious turmoil or civil unrest due to absence or failure or lack of constitutional action or laws that govern diverse societies towards peaceful and harmonious co-existence, or inefficient strategies to manage the sociological impacts of law. Positive inter-religious relations were already modeled by Muhammad (PBUH), through the Medina Charter or through his conduct and approach in volatile and hostile Mecca, just after his migration to Medina. One lesser-known but important contributors of hadith is Asma Binti Abu Bakar, who narrated a hadith on inter-religious relations that is relevant across time. In contemporary times, the state of inter-religious relations is dependent on various factors such as a country’s constitution, laws and social strategies, and the efforts of the government and its religious leaders. The purpose of this study is to analyse the hadith on inter-religious relations. Comparatively, it analysed the model of inter-religious relations in contemporary societies from the global standpoint and within Muslim-majority Indonesia and Muslim-minority Singapore, with a focus on laws and its social impacts. This library-based study is based on a qualitative approach. Primary data was obtained from hadith references, while secondary data was obtained from current research and reports pertaining to the inter-religious relations. The normative approach is engaged in analysing prevalent laws. A descriptive-comparative-deductive approach was used in discussion of the results. The early hadith on inter-religious relations demonstrated the Prophet’s (PBUH) stance and the Islamic approach towards inter-religious relations. There are valuable lessons from this hadith that applies to the Muslim leadership and community. In the context of contemporary and religiously and ethnically diverse societies, the constitution and national laws need to be clear, and all-encompassing, without specific reference to particular groups. Authorities and the Islamic religious leadership need to play active roles in promoting positive inter-religious relations. Corresponding social strategies need to be contextualised to the setting in order to manage differences and complexities.